Crystalline structure and composition of tin oxide film grown by reactive ion assisted deposition as a function of average irradiating energy - Choi, W.K.; Song, S.K.; Cho, J.S.; Jung, H.-J.; Koh, S.K. (Materials Research Society Symposium - Proceedings, 1995)
Tin oxide films with highly preferred orientation along 〈101〉 axis were grown on Si(100) substrate by using reactive ion assisted deposition method. The impinging average ion energy per depositing Sn atom was changed from 10 to 100 eV/atom. Oxygen content in the deposited tin oxide films increased as average impinging ion energy were raised. The maximum XRD peak intensity appeared when the average energy of about 50 eV/atom was applied. From quantitative Auger electron spectroscopy, characteristic transitional Auger peaks of Sn MNN were shifted to lower kinetic energies as much as 4 approx. 6±1.0 eV as the Sn4+ component became dominant in the deposited tin oxide films. On the basis of a tin 3d core level spectra analysis by XPS, it was determined that a sizable chemical shift of 1.0±0.02 eV occurred between stannous tin(Sn2+:SnO) and stannic tin(Sn4+:SnO2). The optical transmittance was also measured in the wavelength range from 200 to 800 nm for tin oxide films deposited on BK7 glass substrate.